TREATMENT AND PREVENTION OF INFLAMMATORY PERIODONTAL DISEASES IN PROFESSIONAL ATHLETES - Hajiyev, J.Q. (World of Medicine and Biology, 2021)
340 athletes were examined. The athletes were divided into 2 treatment groups of 20 patients in each group. Patients of the second group, in addition to traditional therapy, received applications to the gum with propolis for 10 days. Gingivitis index and papillary bleeding index were used to assess the severity of the pathology and the effectiveness of therapeutic and preventive measures. In 16–19 – year- old athletes, sextants with a bleeding rate of 1.40±0.11 are most often detected, that is, gingivitis occurs, while periodontitis of the most severe severity was diagnosed in professional boxers aged 26–32 years, which indicated an insufficient level of periodontal care. At the final stage of clinical trials, the gingivitis index in the main observation group decreased to the minimum value for all groups and terms – 0.63±0.027 points. Whereas, in the control group, the data obtained indicated the development of an inflammatory process of moderate severity – 1.45±0.024 points (p